HUBUNGAN PEMAHAMAN JENIS OPERASI DAN TINGKAT KECEMASAN DENGAN KEMAUAN UNTUK REHABILITASI PADA PASIEN PASCA OPERASI FRAKTUR FEMUR - Prima Saputra, Rinaldi; Wahab Aliun, Fatimah; Zulfikar, Zulfikar; Widagdo, Henry Widagdo (Ensiklopedia of Journal, 2025)
Actions to avoid fracture complications are by carrying out rehabilitation. Patient understanding is very important to improve because if understanding is fulfilled it will help the healing process by carrying out rehabilitation as early as possible and can reduce anxiety in patients.To determine the relationship between understanding the type of surgery and the level of anxiety with the willingness to rehabilitate in patients after femur fracture surgery.The type of research used is quantitative research with an analytical survey research design. Sampling using the Total Sampling technique The number of samples in this study was 30 respondents. The analysis method used is a statistical test using the Kendall tau test.The results of this study indicate that (1) there is a relationship between understanding the type of surgery with the willingness to rehabilitate in patients after femur fracture surgery, the coefficient value of the p-value is 0.011 <0.05 with a closeness value of 0.471. (2) there is a relationship between the level of anxiety with the willingness to rehabilitate in patients after femur fracture surgery, the coefficient value of the p-value is 0.004 <0.05 with a closeness value of 0.555. The results of the hypothesis testing of the anxiety variable have a p-value of 0.472 and the understanding variable has a p-value of 0.014. Suggestion: Physiotherapy is expected to ensure that patients understand the type of surgery they are undergoing and to know the patient's anxiety level in order to increase their willingness to rehabilitate.Keywords: Understanding of types of surgery, anxiety level, willingness to rehabilitate